ANALISIS PERENCANAAN RUTE PENGIRIMAN BARANG MENGGUNAKAN METODE VEHICLE ROUTING PROBLEM (VRP) - Ferdiansyah, Anton; Sholihah, Sita Aniisah; Rifni, Muhammad; Grets, Egi Sirasj; Situmorang, Johan Kiara; Oktaviany, Intan (Institut Transportasi dan Logistik Trisakti, 2021)
The purpose of this study was to determine the optimal route for the delivery of Samsung Electronics goods from Distribution Center (DC) to Retail Stores in the Jabodetabek area. DC functions as a warehouse to deliver goods to the customers. In the distribution of goods to each customer, unoptimal routes is a problem being faced company. This study was designs to determination of the delivery route using the Vehicle Routing Problem (VRP), the Saving Heuristics model. The results show that the mileage is reduced by 19% (107 km), with fuel savings of 20.1% and the total time is reduced by 22.6% or 3.3 hours.